ENHANCING VISUAL ARTS EDUCATION FOR GRADES 5–7 THROUGH DIGITAL TECHNOLOGIES IN GENERAL SECONDARY SCHOOLS - Xamidova Dildora Muhiddin qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Annotation: This article explores strategies for enhancing visual arts education for students in grades 5–7 using digital technologies in general secondary schools. It examines the effectiveness of interactive lessons, multimedia applications, and digital drawing tools in fostering creativity, visual literacy, and practical artistic skills. The study highlights how digital approaches can increase student engagement, individualize learning, and support collaborative artistic projects.